A Correlational Study to Assess the Knowledge and Practices Regarding Catheter-associated Urinary Tract Infection Care Bundle among the Staff Nurses in Selected Hospitals of Maharashtra in View to Prepare the Information Booklet - Veer, Nilesh; Biradar, Vishwanath (Innovational: Journal of Nursing and Healthcare, 2024)
Aim: The purpose of this research is to determine knowledge and practices of staff nurse regarding catheter-associated urinary tract infection (UTIS) care bundle. Methods: The investigator chose to use a descriptive survey approach with a descriptive study design, to investigate the staff nurses’ knowledge of and practices relating to the catheter-associated UTIS care bundle. The sample included 185 nursing staff who were employed in the Intensive Care Unit. Non-probability purposive sampling technique was employed to pick the sample for this study. The analysis of the data included both descriptive and inferential statistical methods. The Karl person co-relation coefficient test used to analyze the correlation and Chi-square test to determine the association between knowledge and practice regarding care for catheter-associated UTIS with demographic variables. Results: The results of this study showed that 101 (54.89%) had moderate knowledge followed by 68 (36.95%) had inadequate knowledge, 15 (8.15%) had adequate knowledge regarding catheter-associated urinary tract infections (CAUTI) Care bundle. 114 (78.26%) had average level of practices, 47 (25.54%) had good level of practices and 23 (12.5%) had poor level of practices regarding CAUTI Care bundle, there is a positive correlation was identified between knowledge and practice, i.e., (r = 0.593). Conclusion: According to the results of this investigation, staff nurses had knowledge and practices about the care bundle for catheterassociated UTIS that were moderate to average. Investigator recommends that the distribution of the informational booklet tool addressing the catheter-associated UTIS care bundle, both the knowledge and the practices will be enhanced.